Risk of Bleeding Related to Selective and Non-selective Serotonergic Antidepressants: A Case/Non-case Approach Using Data from Two Pharmacovigilance Databases - Gahr, M.; Zeiss, R.; Lang, D.; Connemann, B. J.; Hiemke, C.; Freudenmann, R. W.; Schönfeldt-Lecuona, C. (Pharmacopsychiatry, 2015)
Introduction: There is increasing evidence for an association between treatment with selective serotonin reuptake inhibitors (SSRI) and an increased risk of bleeding events. The most important underlying mechanism appears to be inhibition of serotonin uptake in platelets, an effect that is also present in antidepressants with non-selective serotonin-reuptake inhibition (NSRI). Accordingly, also NSRI may be associated with an increased risk of bleeding. However, there is little data in this regard.Methods: Based on data (spontaneous reports of adverse drug reactions) from 2 pharmacovigilance databases (WHO-database/VigibaseTM; BfArM/AkdÄ-database in Germany) we used a case/non-case approach and calculated reporting odds ratios (ROR) as measures for disproportionality regarding the association of treatment with an agent of the group SSRI/NSRI and haemorrhages.Results: Whereas both positive control agents (ASS and diclofenac) were statistically associated with haemorrhages in both databases (ASS: BfArM/AkdÄ, ROR 13.62 [95% CI 12.76−14.53]/WHO, ROR 12.96 [95% CI 12.75−13.16]; diclofenac: BfArM/AkdÄ, ROR 3.01 [95% CI 2.71−3.21]/WHO, ROR 2.11 [95% CI 2.05−2.16]), none of the agents of the group SSRI (ROR<1) was associated with haemorrhages. In group NSRI, only St. John’s wort/hypericum was associated with haemorrhages (WHO-database, ROR 1.31 [95% CI 1.06−1.63]).Discussion: Signal detectioning in 2 pharmacovigilance databases suggest that serotonin reuptake inhibition is not associated with an increased risk of bleeding. However, underreporting may have accounted for the evaluated absent associations, particularly concerning SSRI. Regarding the detected increased risk of bleeding associated with hypericum, pharmacokinetic drug-drug interactions may be relevant independent of serotonin reuptake inhibition.
Keywords: haemorrhages; pharmacokinetics; signal detection; WHO